Skin markers of premature ageing in patients with COPD: results form COSYCONET - Melzer, Thomas; Graf, Veronika; Kronseder, Angelika; Karrasch, Stefan; Kerschner, Martina; Vogelmeier, Claus F.; Bals, Robert; Alter, Peter; Watz, Henrik; Fähndrich, Sebastian Wolfgang; Behr, Jürgen; Waschki, Benjamin; et al. (Journal of Clinical Medicine, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is commonly associated with ageing, with the prevalence and severity increasing by age. Smoking-induced premature ageing is thought to contribute to COPD, particularly lung emphysema. This study aimed to explore the relationship between lung function impairment and skin texture, as a marker of biological or premature ageing, in COPD patients. Methods: A subcohort from the COSYCONET COPD-study was analyzed, where skin-relief replicas of the eye’s outer corner and mid-lower inner arm were collected, along with semi-quantitative facial photographs. We examined the correlation between skin parameters and lung function, particularly the diffusing capacity (TLCO) as an indicator of emphysema. Results: Among 46 COPD patients (69 ± 8 years, 52% female), skin texture from the inner forearm, but not from the eye corner, was significantly associated with TLCO% predicted, with a higher skin roughness correlating with a lower TLCO (p = 0.015). This relationship persisted after adjusting for age, BMI, sex, pack years, and smoking status. No significant associations were found with facial photographs. Conclusions: These findings suggest that systemic ageing, reflected in inner arm skin texture, is linked to lung emphysema. Skin ageing markers may be valuable in future interventional studies involving anti-ageing treatments.